Transformasi Spiritualitas dan Implikasi Teologis dalam Gerakan Kharismatik : Fenomena dan Dampaknya - Patricia Dwi Irwani Telaumbanua; Yosua Altiel Siburian; Elsa Herawati Lubis (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The Charismatic Movement is a spiritual phenomenon that has a significant impact on the lives of Christians, both theologically and socially. This article aims to explore the transformation of spirituality and the theological implications brought about by this movement, as well as its impact on society and culture. The Charismatic Movement emphasizes the active role of the Holy Spirit in the lives of Christians, introducing personal experiences with God through spiritual gifts such as healing, prophecy, and speaking in tongues. The theological implications of this movement include a new understanding of the Bible, the coming of Christ, and the mission of the church in the world. Socially and culturally, the Charismatic movement changed the structure of the church, increased congregational participation in social activities, and introduced changes in views on gender roles and religious education. The social impact of the Charismatic movement can be seen in the spread of more inclusive and dynamic spiritual values, which have an influence on church music and arts culture. The Charismatic Movement strengthens the belief that God is still actively working in the lives of His people through miracles and divine healing. This article shows that the Charismatic movement not only brought about changes in the way Christians live their faith, but also contributed to broader social changes in society, creating Christian communities that were more open, participatory, and relevant to the challenges of the times.